Gender and age-related variations in rumen fermentation and microbiota of Qinchuan cattle - Yueting Pan; Huaxuan Li; Juze Wang; Xiaolei Sun; Entang Liang; Juntao Guo; Jianfang Wang; Ke Zhang; Bingzhi Li; Mengqi Zan; Wucai Yang; Linsen Zan (Animal Bioscience)
Objective Our study aimed to investigate the gender and age-related variations in rumen fermentation, serum metabolites, and microbiota in Qinchuan cattle. Methods A total of 38 Qinchuan beef cattle were selected and maintained on a uniform diet for three months. Rumen fluid and blood samples were collected to determine rumen fermentation, serum metabolites, and microbial 16S rRNA sequencing. Results The results revealed that the concentration of rumen butyrate in female Qinchuan cattle was significantly higher than in males (p<0.05). Isobutyrate, butyrate, and isovalerate exhibited significant age-related differences. Females exhibited lower serum glucose (GLU) and higher triglycerides (TG), nonesterifiedfatty acid (NEFA) levels compared to males (p<0.05). Serum albumin (ALB) and urea (UA) levels increased with age (p<0.05). Furthermore, the alpha diversity of rumen bacteria improved with age (p<0.05), with no gender differences observed. Males had higher relative abundances of Bacteroidota, Verrucomicrobiota, and Cyanobacteria, while females had higher Firmicutes and Desulfobacterota (p<0.05). The cellulose-degrading genus Ruminococcus and propionate-producing genus Succiniclasticum were more abundant in females, whereas the anti-inflammatory genus Lachnospiraceae_NK4A136_group and the hemicellulose-degrading genus Prevotella were more abundant in males (p<0.05). Age-related differences in bacteria were found in Pseudobutyrivibrio and several members of the Lachnospiraceae. Functional prediction indicated that “Amino acid metabolism” and “Lipid metabolism” were mainly enriched in females, whereas “Carbohydrate metabolism” and “Glycan biosynthesis and metabolism” were enriched in males (p<0.05). RDA analysis highlighted butyrate as a key factor influencing the rumen bacterial community. NK4A214_group and Ruminococcus were positively correlated with butyrate, while Prevotella and Pseudobutyrivibrio were negatively correlated with butyrate (p<0.05). Conclusion We observed a significant improvement in the diversity and stability of rumen microbiota as age increased. Ruminococcus, NK4A214_group, and Prevotella were likely contributors to variations in energy utilization and fat deposition between male and female Qinchuan cattle.